1986
DOI: 10.1083/jcb.103.5.1799
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of myogenic differentiation by type beta transforming growth factor.

Abstract: Abstract. Type 13 transforming growth factor (TGFI3) has been shown to be both a positive and negative regulator of cellular proliferation and differentiation. The effects of TGFI3 also are cell-type specific and appear to be modulated by other growth factors. In the present study, we examined the potential of TGFI3 for control of myogenic differentiation. In mouse C-2 myoblasts, TGFfl inhibited fusion and prevented expression of the muscle-specific gene products, creatine kinase and acetylcholine receptor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
229
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(258 citation statements)
references
References 39 publications
20
229
1
2
Order By: Relevance
“…TGF-b inhibits myoblast differentiation in some circumstances (Florini et al, 1986;Massague et al, 1986;Olson et al, 1986;Liu et al, 2001;Rousse et al, 2001) but stimulates it in others (Schofield and Wolpert, 1990;Zentella and Massague, 1992;De Angelis et al, 1998). We investigated whether TGF-b suppresses myoblast differentiation specifically in the context of adult HuSkMC proagated in mitogen-rich medium.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…TGF-b inhibits myoblast differentiation in some circumstances (Florini et al, 1986;Massague et al, 1986;Olson et al, 1986;Liu et al, 2001;Rousse et al, 2001) but stimulates it in others (Schofield and Wolpert, 1990;Zentella and Massague, 1992;De Angelis et al, 1998). We investigated whether TGF-b suppresses myoblast differentiation specifically in the context of adult HuSkMC proagated in mitogen-rich medium.…”
Section: Resultsmentioning
confidence: 98%
“…Myoblast differentiation is induced by reduction of serum and other mitogens in the culture medium (Allen et al, 1997), but some spontaneous differentiation will occur even in mitogen-rich cultures, especially at high cell density. Transforming growth factor b (TGF-b) has been reported by a number of investigators to suppress myoblast differentiation, primarily in studies performed on established cell lines under mitogen-poor conditions that inhibit myoblast proliferation (Florini et al, 1986;Massague et al, 1986;Olson et al, 1986;Liu et al, 2001;Rousse et al, 2001). Contradictory findings of TGF-b effects have been reported in the context of mitogen-rich medium used to culture the L6E9 myoblast cell line (Zentella and Massague, 1992), low cell density (De Angelis et al, 1998), and serum-free media (Schofield and Wolpert, 1990).…”
mentioning
confidence: 99%
“…The inhibition of di erentiation by FGF-2, IGF-1, TGFb, or oncogenic Ras relies on continual signaling (Lathrop et al, 1985;Olson et al, 1986;Clegg et al, 1987;Gossett et al, 1988;Vaidya et al, 1989;Nakafuku et al, 1992). Induction of an autocrine loop would be an e cient mechanism to ensure a continual supply of inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that myostatin, activin, or TGF-b1 impaired myogenic differentiation in cultured myogenic cells from several species. 27,[34][35][36] Using an efficient retroviral gene expression system, we confirmed that these three molecules independently suppressed mouse C2C12 myoblast differentiation. Conversely, the addition of Ki26894 almost completely restored the myotube formation that was impaired by the TGF-b family members.…”
Section: Discussionmentioning
confidence: 53%